Implementation Of Green Accounting And Its Impact On Firm Value: Evidence From Islamic Banking In Indonesia - Ning Wijayanti; Kukuh Trisnafi; Putri Vella Meliyanti; Dedi Suselo; Binti Nur Asiyah; Agus Eko Sujianto (Academic Bright Collaboration, 2026)
Purpose - This study aims to analyze the contribution of green accounting practices to firm value in the banking sector by examining the implementation of sustainability principles at Bank Syariah Indonesia and Bank Aladin Syariah. Methods - The research employed a quantitative-descriptive approach with an associative design using secondary data derived from sustainability reports, financial statements, and stock prices during 2021–2023. Data analysis was conducted through descriptive statistics, the Augmented Dickey-Fuller (ADF) stationarity test, Johansen cointegration test, and the Vector Autoregression (VAR) model using EViews 12.0. Findings – The results indicate that all four green accounting indicators Environmental Costs, Resource Use Efficiency, Environmental Liabilities and Provisions, and Environmental Performance Indicators (EPI) positively contribute to firm value. Statistically, EPI showed the strongest influence on firm value. Descriptively, Bank Aladin demonstrated better efficiency and sustainability reporting performance, while BSI excelled in green financing initiatives and the implementation scale of environmental programs. Research implications – The findings imply that green accounting not only fulfills regulatory and sustainability demands but also enhances transparency, operational efficiency, and investor confidence, thereby supporting sustainable corporate value creation in the banking industry. Originality – This study provides empirical evidence on the relationship between green accounting and firm value in the context of Islamic banking in Indonesia by integrating sustainability indicators with econometric analysis through the VAR approach, which remains limited in previous studies.